Four new species of Heteromysis (Crustacea: Mysida) from public aquaria in Hawaii, Florida, and Western to Central Europe - Wittmann, Karl J.; Abed-Navandi, Daniel (European Journal of Taxonomy, 2021)
Four new species of the subgenus Heteromysis (Olivemysis) were detected in material from (sub)-tropical aquaria in six public aquarium institutions around the globe. Modifications of pleopods by spines represent the strongest structural complex used for differentiation within this subgenus: male pleopods 1–4 modified in H. smithsoniana sp. nov., male pleopods 2–4 plus female pleopod 2 in H. hornimani sp. nov. and H. waikikensis sp. nov. Additional important diagnostic characters are provided by the antennulae, uropods, and telson. The male of H. sixi sp. nov. represents a very rare case within the genus Heteromysis by having only pleopod 2 modified by flagellate spines. The definition of the subgenus Olivemysis is modified in order to include H. sixi sp. nov. A summary of pleopod modifications in the genus Heteromysis and a key to the species of the subgenus Olivemysis are given. The here described new taxa more than double the number of Heteromysis species known from aquaria yet unknown in nature from three to seven.